2019
DOI: 10.13057/biodiv/d200527
|View full text |Cite
|
Sign up to set email alerts
|

Study of the genus Curcuma in Indonesia used as traditional herbal medicines

Abstract: Abstract. Subositi D, Wahyono S. 2019. Study of the genus Curcuma in Indonesia used as traditional herbal medicines. Biodiversitas 20: 1356-1361. Research into local knowledge is very important in providing a database of medicinal plants and as a basis for further research. The genus Curcuma (Zingiberaceae) has been used as medicines and other purposes, so it has a high economic value.  The aim of this study was to record the use of the species of the genus Curcuma as traditional herbal medicines in Indonesia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 10 publications
1
20
0
2
Order By: Relevance
“…From 89 species of medicinal plants used by traditional healers in To Manui ethnic and relevance with previous research (Subositi and Wahyono 2019), it was reported whether Curcuma longa L is the most widely used medicinal plant and has the highest use value index (1.6) (as shown in Figure 1 and Table 1). The species with the highest use value index are actually great importance to the local communities in the case of native species and also very pivotal to be one of the considerations in local biological conservation strategies (Mayo et al 2015).…”
Section: Discussionsupporting
confidence: 52%
“…From 89 species of medicinal plants used by traditional healers in To Manui ethnic and relevance with previous research (Subositi and Wahyono 2019), it was reported whether Curcuma longa L is the most widely used medicinal plant and has the highest use value index (1.6) (as shown in Figure 1 and Table 1). The species with the highest use value index are actually great importance to the local communities in the case of native species and also very pivotal to be one of the considerations in local biological conservation strategies (Mayo et al 2015).…”
Section: Discussionsupporting
confidence: 52%
“…Curcumin, the principal curcuminoid of turmeric (Curcuma longa L.) is known for its capability to block cytokine release (Sordillo & Helson 2015). Plants of the genus Curcuma form an important ingredient in many traditional formulations of South and Southeast Asia (Sanatombi & Sanatombi 2017;Subositi & Wahyono 2019). In addition, a wide variety of species that are traditionally used as foods, might be used to strengthen the immune system, and thus help to prevent the manifestation of COVID-19 (Fan et al 2020).…”
Section: F Merlin Franco 1 Rainer W Bussmannmentioning
confidence: 99%
“…The rhizome of Zingiberaceae is popularly used to treat various ailments, including skin problems, fever, diarrhea and bone injury. There are 1,326 information of uses to treat various ailments using C. longa has been recorded from 644 traditional healers, and 281 information on C. zanthorrhiza from 172 traditional healers, from all over Indonesia (Subositi and Wahyono 2019). However, only two species of Curcuma were found to be used in Rongkong.…”
Section: B I O D I V E R S I T a S 21 (2): 642-651 February 2020 648mentioning
confidence: 99%